Low amplitude and high frequency mechanical stimulation does not affect directly cell differentiation during bone healing - Torres, Libardo Andrés González (2018)
Bone fractures has high incidence and despite its relevance and frequency, some bone healing process features are still unknown. In this work, it is computationally investigated the influence of low amplitude and high frequency mechanical stimulation on cell differentiation during bone healing, using a cell differentiation theory that relates two mechanical variables (strain and flow velocity of interstitial fluid) with the cell fate. For this purpose, a finite element model was developed to study three hypothetical situations, to determine in which proportion external stimulation influences bone healing. Firstly, the mechanical stimulus was computed as 20% of external mechanical stimulus and 80% of the stimulus during gait. Secondly, it was considered 50% external mechanical stimulus and 50% gait stimulus. Finally, it was considered a proportion of 80% external mechanical stimulus and 20% gait stimulus. The results indicated that hypothesis considering high proportions of external stimulation results in unreal delayed healing process and the first hypothetical situation proved to be that which best represents the real process. From the results obtained, it was concluded that external mechanical stimulation does not affected directly cell differentiation during bone healing. Thus, other processes such as flow of oxygen, nutrients or wastes must be considered.